The Impact Of The COVID-19 Pandemic On Foreign Trade - Nuševa, Daniela; Vukmirović, Goran; Marić, Radenko; Macura, Nikola (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Foreign trade is one of the most important ways of including the national economy in international and regional trade flows. Regular exports and imports are considered classic foreign trade transactions, and their volume and structure is one of the basic indicators of the level of economic development. The goal of the foreign trade policy of every national economy is to achieve the highest possible degree of liberalization of its market, primarily through the removal and reduction of trade barriers. However, with the proclamation of the Covid-19 pandemic in March 2020, national economies have introduced various restrictions on movement, both for citizens and for businesses and their outlets. The decline in economic activity has led to the largest decline in global trade. However, international trade began to recover quickly after the initial stagnation, so it is growing today. Exports of certain countries exceeded the levels before the outbreak of the pandemic. This trend is expected to continue, although it must be noted that developed countries have adapted more easily to the current situation, while developing countries are lagging behind. For decades, the foreign trade of the Republic of Serbia has recorded a negative balance, as well as an unfavorable structure of exchange. The aim of this paper is to point out the basic trends and structure of foreign trade transactions of the Republic of Serbia before and after the pandemic, and the need to increase the share of higher processing and added value products in order to improve the country’s competitive position.